Improved approach for LSC detection of 35S aiming at its application as tracer for short groundwater residence times - Schubert, Michael; Kopitz, Jürgen; Knöller, Kay (Journal of environmental radioactivity, 2019)
The knowledge of groundwater residence times in (vulnerable) aquifers is essential for the sustainable management of the associated groundwater resources. A powerful tool for related investigations is the application of naturally occurring radioisotopes as water age indicators. However, due to the limited number of suitable (i.e. omnipresent, short-lived and easily detectable) radionuclides only few studies focus on groundwater ages below one year. A natural radionuclide that does have the potential to cover this time range is 35S (87.4 day half-life). 35S is continually produced in the upper atmosphere and transferred with the rain to the groundwater. Since no natural sources of 35S exist in the subsurface the decrease of the 35S activity concentration in such young groundwater can be used for the determination of its age. Still, 35S activities in precipitation (and hence even more in groundwater) are very low and necessitate appropriate analytical protocols based on liquid scintillation counting (LSC). This turns out to be challenging due to the required large sample volumes and due to potentially high SO42− loads of the samples, both limiting the range of possible applications of 35S as indicator for short groundwater residence times. In the paper we present an improved straightforward LSC based approach for the detection of 35S in natural water samples. We recommend using Insta-Gel Plus as scintillation cocktail for allowing a homogeneous suspension of 35S-containing BaSO4 in the cocktail. The recommended improvements in instrument setting concern the LSC (TriCarb 3170 Tr/SL) counting window, the pulse decay discriminator setting and the delay before burst setting. The settings allow measuring low activity concentrations of 35S, which was previously pre-concentrated from natural water samples, containing SO42− loads of up to 1500mg with a reasonably high statistical reliability.
Gesehen am 30.10.2019